Pay any price greed, power, and endless war - Risen, James (Michigan Brilliance Audio, 2014)
Ever since 9/11 America has fought an endless war on terror, seeking enemies everywhere and never promising peace. In Pay Any Price, James Risen reveals an extraordinary litany of the hidden costs of that war: from squandered and stolen dollars, to outrageous abuses of power, to wars on normalcy, decency, and truth. In the name of fighting terrorism, our government has done things every bit as shameful as its historic wartime abuses ? and until this book, it has worked very hard to cover them up.
Keywords: War on Terrorism, 2001-2009--Economic aspects--United States